1991
DOI: 10.1073/pnas.88.21.9809
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast spectroscopy of the visual pigment rhodopsin.

Abstract: We report on time-resolved absorption studies of the bovine visual pigment rhodopsin with subpicosecond resolution at room temperature. Our data show that bathorhodopsin, rhodopsin's early photoproduct, is photochemically formed in 3.0 ± 0.7 ps. The data suggest that bathorhodopsin formation is kinetically preceded by two species along the rhodopsin-to-bathorhodopsin reaction coordinate. Several years ago, a number of experiments were attempted to determine the kinetic steps during the rhodopsin to bathorhodop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 21 publications
4
52
1
Order By: Relevance
“…This absorption was assigned to molecules having the Franck-Condon geometry. The 620-nm absorption signal at 200 fs was assigned to the 90°-twisted excited state, and it was concluded that ground-state photoproduct was formed in =3 ps (14). This proposed interpretation (14) is inconsistent with the spectral and kinetic results presented here for the following reasons.…”
Section: Methodscontrasting
confidence: 52%
See 2 more Smart Citations
“…This absorption was assigned to molecules having the Franck-Condon geometry. The 620-nm absorption signal at 200 fs was assigned to the 90°-twisted excited state, and it was concluded that ground-state photoproduct was formed in =3 ps (14). This proposed interpretation (14) is inconsistent with the spectral and kinetic results presented here for the following reasons.…”
Section: Methodscontrasting
confidence: 52%
“…2) clearly indicates that there is only a slight change of the absorption band as a function of time. In particular, the constancy of the band shape, bandwidth, and band area are inconsistent with the idea that a transition from the 90°-twisted excited state of the chromophore to the ground-state photoproduct occurs during this time period (14). We expect that the oscillator strength, bandwidth, and band position of the absorption of the 90°-twisted excited state would be significantly different from that of the more planar ground-state photoproduct, as has been suggested theoretically (16).…”
Section: Methodsmentioning
confidence: 53%
See 1 more Smart Citation
“…This species cannot be isolated even at low temperature, and it is identified through a red-shifted, 570-nm max a . Furthermore, the excited-state or ground-state nature of photo Rh is still a matter of debate (40)(41)(42). Given the limited knowledge provided by our computations on the structure of the S 1 reaction path and S 0 relaxation path we cannot presently assign such an entity.…”
Section: Resultsmentioning
confidence: 98%
“…After photon absorption, a series of at least seven intermediates making up the RhRT photosequence appears. These room-temperature intermediates have been identified primarily via transient absorption spectroscopy (3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%